Analyzing effects of political literature: the third-person effect on party members - Syed Abdullah Idid, Syed Arabi; Souket, Rizwanah (2013)
Davison (1983) posited that individuals will perceive mediated messages to have their greatest impact not “on me” or you” but on them- the third person. Research suggests that people judge others to be more influenced than they are by media, advertising, libelous messages, media violence and pornography and television drama. The theory referred to as the Third Person Effect developed on the postulation that audience members would not admit that media had any direct effect on them, but would believe that the media did effect others, the third person (Tewksbury, Moy and Weis, 2004; Price, Tewksbury and Huang, 1998). While people would discount the effects of negative or biased messages, they would, under the notion of the First Person Effect, readily admit being influenced. This study was based on studying the effects of political literature on party and opposition party supporters taking the messages to be positive to one group and biased and partisan to another group. The study focuses on the assumed effects of political literature on own party and opposition party supporters. It traces the degree of influence of Malaysia’s largest political party, Barisan Nasional (BN) political campaign materials on own supporters and on non-BN party supporters. While the Third Person Effect assumes a null or minimal effect on own self and some or strong effect on others, the question that arises are on welcoming favourable media effects on oneself and assuming unfavourable effects on others.